Determination of the Free Term and Leading Coefficient in a Parabolic Equation - Bereznyts'ka, I. B. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider the inverse problem of finding the unknown time-dependent leading coefficient and the free term in a parabolic equation. Boundary conditions and overdetermination conditions are local. We find conditions for the uniqueness and local existence.